Collaborative Governance dalam Pengelolaan Ekowisata Subak di Desa Wisata Jatiluwih, Kecamatan Penebel, Kabupaten Tabanan - Gede Rai Amertha Nara Utama; Komang Adi Sastra Wijaya; I Ketut Winaya (CV. Lenggogeni Data Publishing, 2023)
Jatiluwih Village in Bali is renowned for its subak system. As a tourist village, it's actively enhancing collaborative management to sustain its presence. Collaboration between the village government and residents involves jointly managing Jatiluwih's subak attractions. However, community involvement in its management remains limited. This research aims to grasp the collaborative governance process in developing subak ecotourism management in Jatiluwih. It's a qualitative study using descriptive methods. The analysis draws on the theory of effective collaborative governance. Findings show satisfactory collaboration among the government, private sector, and community, although governmental dominance is an issue. The research results show that collaboration has been running well, with 7 out of 8 indicators showing good performance. The one indicator that needs improvement is the network structure. Recommendations include improving coordination with involved parties, providing understanding to the Jatiluwih community about the benefits of collaboration, and its positive impact on them.